Hierarchy and Information - Rogger, Daniel; Somani, Ravi (World Bank, Washington, DC, 2018)
What determines the distribution of information acquired within the hierarchy of a public organization? Without market processes, the generation and absorption of information in bureaucracy relies on individual actors undertaking costly action to acquire it. This paper reports on comparisons between individual-level claims by public officials in the Government of Ethiopia regarding the characteristics of local constituents they serve and objective benchmark data. Public officials make large errors about their constituents' characteristics. The errors of 49 percent of public officials are at least 50 percent of the underlying benchmark data. Given public officials' stated reliance on this information to make public policy decisions, such mistakes imply a substantial misallocation of public resources. The results are consistent with classic theoretical predictions related to the incentives that determine information acquisition in hierarchies, such as de facto control over decision making and an organizational culture of valuing operational information. A field experiment implies that these incentives mediate the effectiveness of interventions aimed at improving the information of public-sector agents.